The perceptions of women in late marriage / Noor Atiqah Mohd Isa...[et al.] - Mohd Isa, Noor Atiqah; Misri, Nur Aqidah; Fazlan, Muhammad Irfan; Rezali, Nor Shahidatul Nadia; Moktar, Nor Anis Ayuni; Ku Aziz, Ku Aleeza (Faculty of Communication & Media Studies, 2020)
This research will discuss about the perceptions of women in late marriage in Malaysia. This research was also aimed to study the factors of late marriage that commonly happens nowadays, to identify the effects and challenges faced by those who married late, and to determine on how those who married late deal with their surroundings. This research uses a qualitative method which includes a number of seven respondents that aged among 30 and above which is experiencing or has experienced late marriage. The researchers found that it is quite hard for these women to live in this society as they always get negative perceptions from them. In this study, researchers found that there are women who did not get married because of factors that related to their parents, financial, past life and others. According to the informants, most of them did not get married because of their elderly as they have to take responsibilities to take care of them. Therefore, they have all sort of difficulties such as hard to find the right soulmates, infertilities and so on. Some of them also having hard time in dealing with their surroundings because of the stereotyping among the societies regarding this issue.